Isotopologue profiling of the listerial N‐metabolism. Issue 2 (12th February 2016) - Kutzner, Erika; Kern, Tanja; Felsl, Angela; Eisenreich, Wolfgang; Fuchs, Thilo M.
Summary: The nitrogen (N‐) sources and the relative contribution of a nitrogenous nutrient to the N‐pool of the gram‐positive pathogen Listeria monocytogenes are largely unknown. Therefore, 15 N‐isotopologue profiling was established to study the N‐metabolism of L. monocytogenes . The pathogen was grown in a defined minimal medium supplemented with potential 15 N‐labeled nutrients. The bacteria were harvested and hydrolysed under acidic conditions, and the resulting amino acids were analysed by GC‐MS, revealing 15 N‐enrichments and isotopomeric compositions of amino acids. The differential 15 N‐profiles showed the substantial and simultaneous usage of ammonium, glutamine, methionine, and, to a lower extent, the branched‐chain amino acids valine, leucine, and isoleucine for anabolic purposes, with a significant preference for ammonium. In contrast, arginine, histidine and cysteine were directly incorporated into proteins. L. monocytogenes is able to replace glutamine with ethanolamine or glucosamine as amino donors for feeding the core N‐metabolism. Perturbations of N‐fluxes caused by gene deletions demonstrate the involvement of ethanolamine ammonia lyase, and suggest a role of the regulator GlnK of L. monocytogenes distinct from that of Escherichia coli . The metabolism of nitrogenous nutrients reflects the high flexibility of this pathogenic bacterium in exploiting N‐sources that could also be relevant for its proliferation during infection. Abstract : A comprehensive analysis of the listerial N‐metabolism was performed by 15 N‐isotopologue profiling, confirming glutamine and ammonium as preferred N‐sources. Novel findings based on the differential 15 N‐profiles of amino acids are the usage of the branch‐chained amino acids valine, leucine, and isoleucine for anabolic purposes, whereas arginine, histidine and cysteine were directly incorporated into proteins. Methionine, ethanolamine and glucosamine were identified here for the first time as amino donors that feed the core N‐metabolism of Listeria monocytogenes.